Адміністративна відповідальність за порушення правил зупинки, стоянки та паркування транспортних засобів - Салманова, О. Ю.; Salmanova, O. Y.; Комзюк, А. Т.; Komziuk, A. T.; Olena Salmanova; Anatolii Komziuk (Вісник Харківського національного університету внутрішніх справ. – 2021. – № 3 (94). – С. 150-161, 2021)
Визначено сутність, підстави та порядок реалізації заходів адміністративної відповідальності за порушення правил зупинки, стоянки та паркування транспортних засобів, зокрема охарактеризовано зміст правил зупинки, стоянки і паркування цих засобів, порушення яких становить юридичну підставу відповідальності, тобто обʼєктивну сторону складу адміністративного проступку, ознаки субʼєкта, що підлягає відповідальності за ці порушення, адміністративні стягнення, що можуть накладатися за їх вчинення, види субʼєктів, уповноважених розглядати справи про ці порушення, а також особливості провадженння у таких справах. Зроблено висновок, що правове регулювання та практика застосування адміністративних стягнень за вчинення порушень правил зупинки, стоянки і паркування транспортних засобів потребують подальшого вдосконалення, насамперед з погляду забезпечення прав осіб, що притягаються до відповідальності.

The authors of the article have defined the essence, grounds and procedure for implementing administrative liability for violating the rules of stopping, parking, vehicle parking, in particular they characterize the content of the rules of stopping, parking, vehicle parking, violation of which is the legal basis of liability, i.e. the objective aspect of the subject liable for these violations, the administrative penalties that may be imposed for their commission, the types of entities authorized to consider cases of these violations, as well as the specifics of proceedings in such cases. It has been emphasized that driving cars and other vehicles is becoming more intense every year, which is primarily evidence of the success of technical progress. At the same time, the increase in the number of these funds creates a lot of problems for the organization and safety of road trafficking, as well as for the livelihoods of settlements. It is especially true in large cities, where traffic jams often paralyze the entire traffic. In addition, all of these facilities require storage and parking spaces, which are also chronically lacking. It has been concluded that administrative liability for violating the rules of stopping, parking, vehicle parking has many features that are applied to all its components – the grounds for which are violations of specific rules defined by many regulations, and the subject can be recognized not only the person who directly committed these violations, but also other persons who are named responsible by law; content, i.e. administrative penalties that can be applied without taking into account the general rules of their imposition; procedure for implementation, especially in cases of violating the rules of stopping, parking, vehicle parking recorded in the mode of photography (video). The analysis of these features shows that the legal regulation and practice of administrative penalties for violations of the rules of stopping, parking, vehicle parking need further improvement, primarily in terms of ensuring the rights of those prosecuted.

Определены сущность, основания и порядок реализации мер административной ответственности за нарушение правил остановки, стоянки и парковки транспортных средств, в частности охарактеризовано содержание правил остановки, стоянки и парковки этих средств, нарушение которых составляет юридическое основание ответственности.
Administrative Liability for Violating the Rules of Stopping, Parking, Vehicle Parking
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; транспортні засоби; правила зупинки, стоянки та паркування; порушення; адміністративна відповідальність; транспортные средства; правила остановки, стоянки и парковки; нарушения; административная ответственность; vehicles; rules of stopping, parking, vehicle parking; violations; administrative liability